THE EFFECT OF RICE HUSK BIOCHAR AND COW MANURE ON FE AND NI LEVELS AND PATCHOULI PLANT GROWTH ON FORMER NICKEL MINING LAND - Darwis Suleman; Syamsu Alam (Agrisaintifika: Jurnal Ilmu-Ilmu Pertanian, 2026)
Nickel is a fundamental natural resource with high economic value as a raw material for the stainless steel industry, vehicle batteries, electronic products, military weapons, and other industries. Unfortunately, the exploitation of nickel ore through open-pit mining creates a negative impact on the soil and ecosystem. A study was conducted to evaluate the effects of rice husk biochar and cow manure towards the Fe and Ni content and several soil chemical properties and patchouli growth on nickel-mined soil. The study was conducted at the Experimental Farm of the Faculty of Agriculture, Halu Oleo University, from August to November 2023. This study was set up in according to the randomized block design in a factorial pattern in which the first factor was rice husk biochar comprised of without biochar, 75, 150 and 225 g polibag-1, while the second one was cow manure consisted of without cow manure, 75, 150and 225 g polibag-1. The results highlighted the increment of soil pH, CEC and available P due to the application of biochar and cow manure, and conversely the Iron (Fe) and Nickel (Ni) content tended to decrease linearly. Co-application of 3% rice husk biochar and 4.5% cow manure results in successful outcome on soil quality and promotes the dry weight of patchouli plants on nickel-mined soil